Humanities as a Catalyst for Innovation in Contemporary Education and Society - Sokip; Syafi’i, Asrop; ‘Azah, Nur; El-Yunusi, Muhammad Yusron Maulana; Mardiyah (Journal of Studies in Academic, Humanities, Research, and Innovation, 2024)
This study aims to analyze the role of humanities as a catalyst in educational and social innovation. In an increasingly interconnected world, humanities offer an approach that fosters critical thinking, creativity, and social awareness among students, which are essential for addressing contemporary social and cultural challenges. Therefore, understanding how humanities can be integrated into education to promote positive social change is crucial. This research uses a library research method, collecting and analyzing relevant literature on the application of humanities in education and its impact on society. The findings indicate that incorporating humanities into the educational curriculum can enhance students' understanding of social issues, strengthen character, and improve critical thinking skills. Furthermore, the study reveals that humanities play a role in facilitating social innovation by encouraging student involvement in community activities and raising awareness about the importance of human values. Despite challenges such as lack of policy support and inadequate resources, this study suggests strengthening humanities-based education through supportive educational policies, as well as innovative teaching methods and training